Association between serum lipase levels and chronic kidney disease stages - Gui Zhang; Zuojie Li; Cheng Xin Xu (PLoS ONE, 2025)
Objective To explore the relationship between serum lipase levels and chronic kidney disease (CKD) progression, evaluating its usefulness in assessing efficacy, severity, and predicting outcomes in CKD. Methods This retrospective study analyzed 251 CKD patients treated at our hospital from January 2018 to December 2023, categorizing them into four groups based on 2022 Chinese and 2024 KDIGO guidelines. Clinical and biochemical data, including serum lipase, Scr, and BUN were collected. Additionally, a supplementary cohort of 50 CKD patients treated between January 2024 and March 2025 was included to support the findings. Results Serum lipase levels increased with advancing CKD stages [G1-2: 40.50 (30.75,52.00), G3:47.00 (37.25,61.00), G4:100.00 (77.00,126.00), G5:155.50 (126.75,243.75), (P < 0.05), showing a positive correlation with Scr (r = 0.714, P < 0.001) and BUN ((r = 0.678, P < 0.001). Univariate logistic regression analysis indicated that age, Scr, BUN, and serum lipase were positively associated with CKD stages, whereas HDL-C exhibited negative correlations. Multivariate logistic regression analysis identified several associated factors of CKD stages, including Scr (OR=1.01; 95% CI 1.01–1.02; P < 0.001), BUN (OR=1.17; 95% CI 1.07–1.29; P < 0.001), age (OR=1.03; 95% CI 1.01–1.05; P = 0.019), and serum lipase (OR=1.02, 95% CI 1.01–1.03, P < 0.001). Serum lipase’s AUC for distinguishing CKD stages G1-2 vs. G3, G3 vs. G4, and G4 vs. G5 were 0.64 (0.55–0.73), 0.89 (0.83–0.94), and 0.84 (0.75–0.93), respectively, with validation cohort AUCs of 0.65 (0.45–0.85), 0.82 (0.62–1.00), and 0.86 (0.65–1.00). Conclusions Serum lipase emerges as a novel biomarker for CKD stages, exhibiting stage-dependent increases and independent prognostic significance. Regular testing could improve risk assessment and complement current markers like eGFR and proteinuria, enhancing CKD management.